Media Konkret Sebagai Upaya Meningkatkan Kemampuan Mengungkapkan Kalimat Permintaan Maaf Pada Kelas II SD - Taufiq Ardy Cahyono; Himmatul Ulya; Ristiyani Ristiyani (Jurnal Prakarsa Paedagogia, 2020)
This study aims to descrie the concrete media as an effort to improve the ability to express a sentence of apology i elementary school. The research method used is classroom action research. The subject of this study as much 24 student. Data collection techniques using interviews , observation and test. Concrete media is an object in the form of real or artificial object that have been used by teachers in conducting learning with the aim of student being able to easily understand the learning material. The result show that concrete media can improve the ability to express apology setences. Cycle I student complete with a percentage 77% and which is incomplete with a percentage 23% whie the cycle II student complete with a percentage 91% and which is incomplete with a percentage 9%.